Analisis Pengaruh Ekspor, Nilai Tukar, dan Inflasi terhadap Cadangan Devisa Indonesia Tahun 2018-2023 - Munggaran, Fajar Rakean; S, Suripto (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Foreign exchange reserves are an important monetary indicator that demonstrates the economic strength of a country. The size of the foreign exchange reserve is determined by the international economic activities carried out by the country with various factors that influence it. This research aims to determine the influence of exports, exchange rates, and inflation on foreign exchange reserves in Indonesia. The data used in this research is secondary data spanning from 2018 to 2023. The analytical method used in this research is multiple regression using the Eviews 12 software system. The results indicate that, partially, exports have a positive and significant effect on foreign exchange reserves, the exchange rate variable has no effect on foreign exchange reserves and inflation has a negative and significant effect on foreign exchange reserves. Exports, exchange rates, and inflation simultaneously have a significant influence on foreign exchange reserves.